The Impact of Modality on Mind Wandering during Comprehension. Issue 1 (15th September 2015) - Kopp, Kristopher; D'Mello, Sidney
Summary: The executive resource hypothesis assumes a positive relationship between resource availability and mind wandering. Under the assumption that different modalities of information delivery differentially tax resources, we compared mind wandering across different modalities during the presentation of The Red Headed League (Experiment 1 and 2) and Walden (Experiment 3). An Audio only condition produced the most mind wandering. Two conditions that presumably consumed more executive resources than the Audio Only condition (i.e. Audio + Text and Self‐paced Reading) produced equivalent amounts of mind wandering during Experiments 1 and 2. In Experiment 3 the reading time of the Self‐paced readers moderated the effect of mind wandering in that the fast readers mind wandered more than those in the Audio + Text condition. Results are discussed in the context of the demands of different modes of information delivery methods and mind wandering as well as the potential effects of material type. Copyright © 2015 John Wiley & Sons, Ltd.